Log-Periodic patch antenna with tunable frequency - A. Rahim, Mohamad Kamal (IEEE, 2011)
This paper describes the design and analysis of a Log-Periodic Microstrip Antenna Array operating between 3.3 Gigahertz (GHz) and 4.5 GHz. A five square patches fed by inset feed line technique are connected with a single transmission line by a log-periodic array formation. By applying five PIN Diodes at the transmission line with a quarter-wave length radial stub biasing, four different sub-band frequencies are configured by switching ON and OFF the PIN Diode. Simulation as well as measurement results with antenna design is presented and it shows that a good agreement in term of return loss. The simulated radiation pattern and realized gain for every sub bands also presented and discussed.